2020
DOI: 10.1186/s13550-020-00666-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the predictive power of high skeletal muscle uptake of FDG in amyotrophic lateral sclerosis

Abstract: Background: We recently reported that enhanced [18F]-fluorodeoxyglucose (FDG) uptake in skeletal muscles predicts disease aggressiveness in patients with amyotrophic lateral sclerosis (ALS). The present experimental study aimed to assess whether this predictive potential reflects the link between FDG uptake and redox stress that has been previously reported in different tissues and disease models. Methods: The study included 15 SOD1 G93A mice (as experimental ALS model) and 15 wildtype mice (around 120 days ol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…This response is not related to measurable alterations in cytosolic glucose degradation machinery. By contrast and in agreement with previous observations in different organs and tissues [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], it closely matches the response of H6PD catalytic function and, thus, the rate of a PPP selectively located within the ER. Since a major PPP role is the reduction of NADP to NADPH to feed the glutathione-dependent response to oxidative stress [ 27 , 28 ], the selective decrease in H6PD catalytic function suggests a greater vulnerability of the posterior cortex to the increased generation of ROS associated with prolonged hyperglycemia [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This response is not related to measurable alterations in cytosolic glucose degradation machinery. By contrast and in agreement with previous observations in different organs and tissues [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], it closely matches the response of H6PD catalytic function and, thus, the rate of a PPP selectively located within the ER. Since a major PPP role is the reduction of NADP to NADPH to feed the glutathione-dependent response to oxidative stress [ 27 , 28 ], the selective decrease in H6PD catalytic function suggests a greater vulnerability of the posterior cortex to the increased generation of ROS associated with prolonged hyperglycemia [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Fourteen days thereafter, all mice were fasted for 12 h, weighed, and anesthetized with intraperitoneal administration of ketamine 100 mg/kg (Imalgene, Milan, Italy) and xylazine 10 mg/kg (Bio98, Italy). FDG imaging was performed as previously described [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Briefly, serum glucose level measurement and animals were positioned in a dedicated micro-PET system (Albira, Bruker, USA), and FDG (3–4 MBq) was injected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may in part have been driven by the acidosis that develops during ALS, which can cause a shift to glycogen synthesis over lactate production [ 89 , 95 , 96 ]. FDG-PET studies of SOD1-G93A mice suggested that glucose retention was significantly higher in muscle, although activity of PFK, the rate limiting enzyme in glycolysis, was significantly decreased [ 97 ]. Increased glucose uptake is hypothesised to be a response to increased hexose-6-phosphate dehydrogenase activity, an enzyme from the PPS, highlighting how increased glucose uptake/retention is not indicative of increased glycolysis.…”
Section: Glycolytic Changes In Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…In SOD1 G93A mice, acidosis develops in the blood, spinal cord and brain stem towards the end stage of the disease [ 96 ]. Serum changes in pH were attributed to changes in strong ion gap [ 97 ], a measure which takes into account common strong and weak acids in the blood, indicating an unidentified anion is responsible for blood acidosis.…”
Section: Glycolytic Changes In Amyotrophic Lateral Sclerosismentioning
confidence: 99%